2000
DOI: 10.3758/bf03198411
|View full text |Cite
|
Sign up to set email alerts
|

The selection of homograph meaning: Word association when context changes

Abstract: In a study of lexical ambiguity processing, responses to homographs were examined in a word association task. The context of repeated exposures of a homograph was manipulated by requiring a response to a word related to a meaning of the homograph on the trial prior to homograph presentation. A change of that relationship reduced the effectiveness of the contextual item as a prime on the second occurrence of the homograph. In response to a third unprimed occurrence of the homograph, associations were consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
22
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 17 publications
3
22
1
Order By: Relevance
“…Importantly, the attentionbased process of meaning facilitation and inhibition appears particularly robust in normal subjects, as this pattern of priming was maintained when the proportion of dominant and subordinate biased pairs was manipulated and when subjects were instructed to focus on less frequent meanings. This view is supported by Gorfein et al (2000) who reported that, when opposing semantic contexts are presented before an ambiguous word, a primacy effect is attained whereby processing of one meaning of an ambiguous word results in the inhibition of alternative meanings.…”
Section: Models Of Ambiguous Word Processingsupporting
confidence: 67%
“…Importantly, the attentionbased process of meaning facilitation and inhibition appears particularly robust in normal subjects, as this pattern of priming was maintained when the proportion of dominant and subordinate biased pairs was manipulated and when subjects were instructed to focus on less frequent meanings. This view is supported by Gorfein et al (2000) who reported that, when opposing semantic contexts are presented before an ambiguous word, a primacy effect is attained whereby processing of one meaning of an ambiguous word results in the inhibition of alternative meanings.…”
Section: Models Of Ambiguous Word Processingsupporting
confidence: 67%
“…The primacy effect obtained by Gorfein et al (2000) does not appear to be predicted by any published model of ambiguity processing. With the assumption that the inhibition of the nonselected meaning carries over across presentations of an ambiguous word, the variety of suppression and/or inhibitory mechanisms postulated in the literature can account for the reduction in priming that is obtained when the second presentation of the homograph occurs in a meaning context different from that of the first presentation.…”
mentioning
confidence: 72%
“…Although the present study is an extension of Gorfein et al (2000), it differs in a number of important ways. The use of the expanded Gorfein and Walters (1989) picture/ word orienting task instead of a more standard semantic priming manipulation makes the local context in Phase 1 of the present study entirely different from that in the critical Phase 3: Both the stimuli serving to prime the meaning of a homophone and the required response differ.…”
mentioning
confidence: 99%
See 2 more Smart Citations